1999
DOI: 10.1163/22941932-90001550
|View full text |Cite
|
Sign up to set email alerts
|

Perforated Ray Cells in Saracha Quitensis (Solanaceae)

Abstract: This work reports perforated ray cells in the stem wood of Saracha quitensis (Solanaceae), In this species the perforated ray cells were found either isolated or together in groups of 2 to 4, localised mainly on the ends of multi seriate rays, though they may also be observed in the ray body. They are generally larger than other ray cells, with simple perforations, as in vessel elements, located in both radial and tangential walls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…1, 2, 7-11) (Table 1). The combined presence of simple and multiple perforation plates in PRCs in the wood of the same species has been reported more often (McLean & Richardson 1972;Nagai et al 1994;Otegui 1994;Eom & Chung 1996;Ceccantini & Angyalossy-Alfonso 2000) than the presence of exclusively simple perforation plates (Botosso & Gomes 1982;Lindorf 1999;Terrazas 2000;Agarwal et al 2002;Serdar et al 2004). When comparing the perforation plate type of the PRCs with those of the VEs (Table 1), we found both similar and different plates in roots and branches in the studied species.…”
supporting
confidence: 64%
“…1, 2, 7-11) (Table 1). The combined presence of simple and multiple perforation plates in PRCs in the wood of the same species has been reported more often (McLean & Richardson 1972;Nagai et al 1994;Otegui 1994;Eom & Chung 1996;Ceccantini & Angyalossy-Alfonso 2000) than the presence of exclusively simple perforation plates (Botosso & Gomes 1982;Lindorf 1999;Terrazas 2000;Agarwal et al 2002;Serdar et al 2004). When comparing the perforation plate type of the PRCs with those of the VEs (Table 1), we found both similar and different plates in roots and branches in the studied species.…”
supporting
confidence: 64%
“…The observations of these authors were later confirmed by numerous studies with species from different families (e.g., Serdar et al 2004;Joffily et al 2007). However, some exceptions have been reported for species that have homocellular to weakly heterocellular rays as in Miconia ternatifolia (Chalk & Chattaway 1933;Rao et al 1984;Lindorf 1999).…”
mentioning
confidence: 73%
“…The variation in armature may be taxonomically useful as spines are restricted to the Dunalia + Eriolarynx + Saracha + Vassobia clade (Smith and Baum, 2006). Anatomical variation has not been extensively explored in Iochrominae, aside from a study of ray cells in Saracha (Lindorf, 1999). In contrast, many biochemical studies focused on Iochroma and related genera (e.g., Lischewski et al, 1992;Alfonso et al, 1993) and have uncovered a wide variety of novel withanolides.…”
Section: Floral Trait Evolutionmentioning
confidence: 99%